Fred A. Carlson papers - Carlson, Fred A.
Shorthand notebooks, stenographic reports, notes, bulletins, analytical tables, copy of armistice terms, biographical information on conference delegates, maps, and other materials pertaining primarily to Carlson's service at the Paris Peace Conference (1919-1920) as a reporter with the American Commission to Negotiate Peace and to the postwar treaty with Germany. Includes Carlson's obituary and some materials relating to his career as a court and congressional reporter.
Court reporter, journalist, and soldier.
Collection material in English.
Keywords: United States. -- American Commission to Negotiate Peace; United States. -- Congress -- Reporters and reporting; World War, 1914-1918 -- Treaties; Germany -- Foreign relations -- United States; United States -- Foreign relations -- Germany; United States -- Foreign relations -- 1913-1921.; Journalists; Law reporters; Soldiers